The Schizosaccharomyces pombe spo20(+) Gene Encoding a Homologue of Saccharomyces cerevisiae Sec14 Plays an Important Role in Forespore Membrane Formation - Nakase, Yukiko (The American Society for Cell Biology, 2001)
The Schizosaccharomyces pombe spo20-KC104 mutation was originally isolated in a screen for sporulation-deficient mutants, and the spo20-KC104 mutant exhibits temperature-sensitive growth. Herein, we report that S. pombe, spo20(+) is essential for fission yeast cell viability and is constitutively expressed throughout the life cycle. We also demonstrate that the spo20(+) gene product is structurally homologous to Saccharomyces cerevisiae Sec14, the major phosphatidylinositol transfer protein of budding yeast. This structural homology translates to a significant degree of functional relatedness because reciprocal complementation experiments demonstrate that each protein is able to fulfill the essential function of the other. Moreover, biochemical experiments show that, like Sec14, Spo20 is a phosphatidylinositol/phosphatidylcholine-transfer protein. That Spo20 is required for Golgi secretory function in vegetative cells is indicated by our demonstration that the spo20-KC104 mutant accumulates aberrant Golgi cisternae at restrictive temperatures. However, a second phenotype observed in Spo20-deficient fission yeast is arrest of cell division before completion of cell separation. Consistent with a direct role for Spo20 in controlling cell septation in vegetatively growing cells, localization experiments reveal that Spo20 preferentially localizes to the cell poles and to sites of septation of fission yeast cells. We also report that, when fission yeasts are challenged with nitrogen starvation, Spo20 translocates to the nucleus. This nuclear localization persists during conjugation and meiosis. On completion of meiosis, Spo20 translocates to forespore membranes, and it is the assembly of forespore membranes that is abnormal in spo20-KC104 cells. In such mutants, a considerable fraction of forming prespores fail to encapsulate the haploid nucleus. Our results indicate that Spo20 regulates the formation of specialized membrane structures in addition to its recognized role in regulating Golgi secretory function.